Analisis Pengaruh Corporate Governance dan Risk Management Committee Terhadap Financial Performance Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Tasya, Dhea Saummi; Gandakusuma, Imo (UI Scholars Hub, 2022)
The aim of this study is to analyze the effect of corporate governance and risk management committee of manufacturing firms at the Indonesia Stock Exchange in 2016 – 2020. In 2016-2020, manufacturing companies were the highest contributors to national income, and financial performance fluctuated. Manufacturing companies do not yet have specific regulations governing corporate governance mechanisms, so this research is needed. The results of this study find that the existence of a risk management committee has insignificant on financial performance. The auditor reputation and the independence of the audit committee has insignificant on financial performance through the existence of a risk management committee. The size of the board of commissioners, the frequency of board meetings, and the risk of financial reporting has positively significant on financial performance through the existence of a risk management committee.